2018
DOI: 10.17844/jphpi.v21i1.21454
|View full text |Cite
|
Sign up to set email alerts
|

Produksi Pigmen dan Identifikasi Kapang Penghasilnya Menggunakan Pendekatan DNA Barcoding

Abstract: Kapang endofit laut diketahui sebagai sumber berbagai senyawa bioaktif yang berguna bagi kesehatan. Penelitian yang telah dilakukan sebelumnya membuktikan bahwa kapang endofit isolat RS3 asal tanaman pesisir <em>Hydnophytum formicarum</em> asal Sorong menghasilkan pigmen hitam dengan potensi sebagai fotoprotektor namun pada penelitian tersebut tidak memiliki data mengenai produksi pigmen serta identifikasi kapang penghasilnya. Penelitian ini bertujuan untuk menentukan produksi pigmen hitam asal kap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Sibero et al stated that fungal pigment had antibacterial activity against multidrugresistant (MDR) human pathogen such as ESBL Escherichia coli, S. enterica ser. Typhi, S. haemolyticus, methicillin-resistant Staphylococcus aureus (MRSA), and Klebsiella pneumoniae [4,5,11]. Ji and Kim [18] also reported that the pigment produced by Serratia sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sibero et al stated that fungal pigment had antibacterial activity against multidrugresistant (MDR) human pathogen such as ESBL Escherichia coli, S. enterica ser. Typhi, S. haemolyticus, methicillin-resistant Staphylococcus aureus (MRSA), and Klebsiella pneumoniae [4,5,11]. Ji and Kim [18] also reported that the pigment produced by Serratia sp.…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, the methanol solvent was evaporated using a rotary evaporator at 40 °C, while the ethyl acetate solvent at 37 °C. Then, the crude extract was then weighed, wrapped with aluminium foil, and stored in a freezer [11].…”
Section: Secondary Metabolites Extractionmentioning
confidence: 99%
“…Moreover, in this study we also applied DPPH reagent to visualize some spots with antioxidant properties. Interestingly, some potential spots which indicated by the presence of white or yellowish colour were appeared after the reagent spraying [25]. The n-hexane extract had 2 yellow spots, whereas ethyl acetate and methanol extract demonstrated 3 yellow spots.…”
Section: Resultsmentioning
confidence: 99%
“…Total Phenolic contents was expressed as mg GAE (Gallic Acid Equivalents). [25]. The pathogenic bacteria were inoculated onto Mueller-Hinton agar (MHA, HiMedia) while the fungi were revived onto Potato Dextrose Agar (PDA, HiMedia) using a streak method and incubated for 24 hours at 37 o C. On the screening day, the pathogens were suspended into Nutrient Broth (NB, Himedia) with 0,5 McFarland (HiMedia).…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%
“…ITS 1 primary as forward and ITS 4 as reverse was chosen because the primary was in its conservative loci region for DNA amplification from fungi (Sibero et al, 2018b). The location of the primary conservative areas of ITS 1 and ITS 4 can be seen in Figure 5.…”
Section: Activity Of Proteolyticmentioning
confidence: 99%